Hubungan Frekuensi Konsumsi Junk Food, Status Gizi, dan Massa Lemak Tubuh dengan Usia Menarche pada Anak Sekolah - Putri May Wahyu Laili; Lailatul Muniroh; Zulfa Taqiyyah Ramadhani (Media Gizi Kesmas, 2024)
Background: Menarche is the onset of menstruation for the first time in women. Menarche can be a sign of reproductive organ maturity. On average, menarche occurs at the age of 12-13 years, but in recent years the age of menarche has shifted to a younger age. Based on the 2018 Riskesdas, the average age of menarche in Indonesia has decreased by 0.6 years since 2010. Objectives: To analyze the relationship between frequency of junk food consumption, nutritional status, and body fat mass as factors of age at menarche. Methods: A cross-sectional design was used in this study. This study involved students who had experienced menarche in grades IV, V, and VI of SDIT At-Taqwa Surabaya. The study sample was 47 students who were selected using simple random sampling method. Data on the frequency of junk food consumption was obtained using FFQ form, nutritional status using BAZ, and body fat mass using Bioelectrical Impedance Analysis (BIA). Spearman correlation test was used to analyze the data. Results: It was found that the average age of menarche of female students was 10.1 years and as many as 65.9% experienced early menarche. Most of the students consumed junk food frequently sometimes, had more nutritional status, and healthy category fat mass. The results of data analysis show that there is a relationship between the frequency of fast-food consumption (p=0.045, r=-0.249), frequency of snack consumption (p=0.017, r= 0.348), nutritional status (p=0.007, r=-0.389), and body fat mass (p=0.018, r=-0.343) with the age of menarche of school children. Conclusion: The higher the frequency of fast food and snack consumption, nutritional status, and body fat mass, the earlier the age of menarche.